Evaluating the dynamic‐mechanical and thermal stability of polyphenylene sulfide composites filled with magnetic filler for sensor applications. (28th March 2022) - Aloui, Sahbi; El Yaagoubi, Mohammed; Münster, Bernhard; Schwegler, Dietmar
Abstract: Isotropic polyphenylene sulfide (PPS) composites filled with the magnetic fillers strontium ferrites (SrFeO) and neodymium iron boron (NdFeB) at two concentrations of 52 vol.% and 60 vol.% were prepared by the injection molding technique without use of an external magnetic field. Frequency sweeps shows that the mechanical frequency has little influence on the strength of all PPS samples and only ensures a higher mobility of the PPS chain ends at high frequency. Increasing the magnetic filler content and the use of NdFeB instead of SrFeO provide the PPS composites a larger structural robustness making them more resistant to mechanical loads and mechanically more stable. The temperature behavior of the PPS composites shows independently of the filler a strong softening from 80 °C. Nevertheless, larger operating temperatures below the glass transition temperature appear realistic. Abstract : Variation of the loss factor tan δ as a function of the temperature of polyphenylene sulfide (PPS) samples filled with strontium ferrite and neodymium iron boron at a frequency of 10 Hz and dynamic strain amplitude of 0.02 %.